A pedagogical journey into the English classroom at Célimo Rueda School in Cali – Valle: My experiences as an English teacher with 3th graders (2018)
The purpose of this research was to illustrate pedagogical reflections and the teaching practice in the language classroom. The research was carried out with third graders at Célimo Rueda School in Cali. One group participated in the inquiry through of a pedagogical proposal, which were applied by a series of strategies and activities to bring the students something different that let them living new experiences, and to answer the main question about how does the English teacher’s narrative could illustrate those pedagogical reflections and teaching practices. The research involves qualitative data; the information was collected through a teacher’s journal, students’ artifacts and video recordings. The data analysis was conducted subjectively and descriptively by the researcher; the findings of the study indicated that students could face and participated in meaningful situations into the classroom which were related with their context and also helped to improved students and teacher’s performance and attitude; besides it gave to the participants the opportunity to tell the story by themselves while took part on it.